Keeping heads above water : Salvadorean refugees in Costa Rica - Basok, Tanya, 1958- (McGill-Queen's University Press, 1993)
Costa Rica has a long-established humanitarian tradition as a country of asylum for refugees fleeing repressive regimes in other South American countries. Salvadorean refugees began arriving in Costa Rica in 1980, and many of them received assistance directed at making them self-sufficient. In Keeping Heads Above Water Tanya Basok focuses on the urban development programs funded and implemented by various international and domestic, governmental and non-governmental agencies. Basing her study on extensive field-work with Salvadorean refugees, she addresses the questions of why some small urban refugee enterprises failed, and how and why others survived and flourished.